Extended Transpalatine Approach for Excision of Juvenile Angiofibroma - Josefino G. Hernandez; Arsenio A. Cabungcal; Ryner Jose D. Carrillo (Philippine Journal of Otolaryngology Head and Neck Surgery, 2015)
Objective:  To describe the extended transpalatine approach (ETPA) with transection of the ipsilateral greater palatine artery and extension of the ipsilateral retromolar incision and its corresponding surgical outcomes and present it as an option in the excision of juvenile angiofibroma (JA).